Comparing seismic performances of pilotis and bare RC frame structures by shaking table tests. (15th November 2019) - Gong, Maosheng; Zuo, Zhanxuan; Wang, Xiaomin; Lu, Xiaotong; Xie, Lili
Highlights: Shaking table tests are carried to compare the performances of RC frames. The infill walls change the failure mode and damage distribution of the frames. Provides valuable test data to verify analytical and/or numerical failure analysis. The collapse prevention threshold in the seismic codes may be conservative. Abstract: This study investigates the role of masonry infill walls in the responses and failure modes of RC frames subjected to earthquake, by applying shaking table tests on two three-story, two-bay, 1/4-scale RC frame structures. Two types of RC frame structures, an infilled RC frame without infill walls in the first story (pilotis frame) and a bare RC frame, are constructed according to the seismic design codes of China. The pilotis and bare frames are simultaneously deployed on a shaking table when I-ELC180 ground motion and Wolong ground motion excitations are used. The two specimens are subjected to a sequence of dynamic tests with increasing intensity. This paper mainly presents and compares the phenomena observed from the shaking table tests of the pilotis and bare frames, including the dynamic properties, acceleration and displacement responses, evolution of damage and final failure mechanisms. The tests indicate that, compared with the bare frame, the infill walls in the pilotis frame can significantly affect the failure mode and damage distribution. Plastic hinges first appear in the 1 st story columns for the pilotis frame under seismic loading, while plastic hinges first appear at the beam ends in the 1 st story for the bare frame; The damage to the pilotis frame is increasingly concentrated in the 1 st story as the earthquake intensity increases, while the damage distribution along the height of the bare frame remains almost the same as the earthquake intensity increases. The maximum interstory drift ratio of the pilotis frame is up to 50% larger than that of the bare frame under the same earthquake intensity.